Comparison of Complex Training with Resistance Training on The Performance of Futsal Athletes - Dita Oktavianto; Dedi Supriadi; Silvy Juditya (Universitas Negeri Semarang, 2026)
The purpose of study assesses the effectiveness of complex training CT and resistance training RT to enhance sprint speed and leg explosive power and agility and anaerobic capacity of futsal athletes. The research used a quasi-experimental pretest-posttest control group design to study 30 male futsal players aged 15 to 17 who were divided into two groups through random assignment to the CT group n 15 and the RT group n 15. The two groups participated in eight weeks of training which took place three times each week. The researchers used the Tests Sprint 20 Meter and Vertical Jump Test and Illinois Agility Test and Running Anaerobic Sprint Test (RAST) to assess athlete performance. The researchers used paired t-test and independent t-test for data analysis with a significance level of α = 0.05. The study results demonstrated that both training methods produced significant improvements across all performance measurement variables. The CT group outperformed the RT group in their increases for both leg explosive power and anaerobic capacity. The two groups showed no statistically significant differences in their sprint speed and agility performance. The research findings show that complex training functions as a more effective conditioning method which enhances explosiveness and anaerobic capacity in futsal players through Post-Activation Potentiation (PAP) mechanisms.